Statistics Easy Tool (SET) / Noor Aisyah Idris and Nurdia Azlin Ghazali - Idris, Noor Aisyah; Ghazali, Nurdia Azlin (2021)
The concept of statistics which requires firm understanding of the application and memorizing formula is not easy for new learners, especially for social science background undergraduates. With existing learning tools, students still have problems utilizing it because they tend to forget formulas and the steps that need to be carried out to produce the analysis. This study explores the learning tool needed by undergraduates who are learning statistics courses. This study also aims to develop an interactive learning tool called Statistics Easy Tool (SET) based on Microsoft Excel on descriptive analysis and linear regression analysis. In this study, it is found that most of the students have difficulties understanding and memorizing the steps to extract value from a calculator by only watching the video or guideline given. Result also indicates that 85.5% of the students agree that they need one tool that helps find all values just in one-time data entry and most of them need a tool that provides an explanation about value calculated from the analysis. SET can be used as a powerful learning tool to undergraduates to explore abstract concepts in statistics, to run analysis with just one click and definitely to make learning statistics more interesting and effective. Moreover, it has the potential to be commercialized to undergraduates especially for non-science undergraduates as well as educators in Universiti Teknologi MARA.